The Role Of Hots Learning As An Effort To Improve Critical Thinking On Students In Communication Science Reviews - Mavianti Mavianti; Rizka Harfiani (Proceeding International Seminar of Islamic Studies, 2019)
Talking about HOTS is not just about subjects that students must master so they are able to answer questions that arise during exams. HOTS is the final goal to be achieved through approaches, processes and learning methods. Mistakes in understanding HOTS will have an impact on the ultimate goal to be achieved. In this case the teacher has a very important role in applying HOTS to students. This article will discuss how a teacher should be able to carry out his role so that the HOTS learning that is carried out can have an impact that is able to improve students' ability to think critically. And in the study of communication science, a teacher must really understand the communication process so that in the delivery of material can choose the appropriate approach so that it supports the learning process by using appropriate learning methods. So that when there is misunderstanding in students, the teacher can evaluate. Because in theory, the communication process is a systemic thing. That is, each component involved in communication has their respective roles which as a whole are a unity that cannot be separated from each other. And each component is also inseparable from internal and external factors that can influence when communication occurs, which is when the learning process.